Peculiarities in the classification and administration of mobility aids for people with defects and diseases of their locomotor system - Saleeva, Antonina; Shchetуnin, Victor; Chernyshov, Aleksandr; Kudryavtseva, Tatyana; Palub, Tamara; Karpenko, Kira; Matveeva, Larysa (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2014)
The article presents results of the work on systematization of the nomenclature list of walking aids, controlled by one hand (crutches, canes) and by two hands (rollator walkers and walking frames), which are used by patients and invalids during their treatment and rehabilitation, as well as results of the work on development of catalogues for these kinds of technical means of rehabilitation. The documents were executed in compliance with International Standard ІSO 9999:2002.